2021
DOI: 10.3390/rs13224608
|View full text |Cite
|
Sign up to set email alerts
|

Subtidal Natural Hard Substrate Quantitative Habitat Mapping: Interlinking Underwater Acoustics and Optical Imagery with Machine Learning

Abstract: Subtidal natural hard substrates (SNHS) promote occupancy by rich benthic communities that provide irreplaceable and fundamental ecosystem functions, representing a global priority target for nature conservation and recognised in most European environmental legislation. However, scientifically validated methodologies for their quantitative spatial demarcation, including information on species occupancy and fine-scale environmental drivers (e.g., the effect of stone size on colonisation) are rare. This is, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…In the current Belgian MSP (MSP; 2020-2026) it is designated as a search zone for biodiversity protection as well as a prospecting area for marine aggregate extraction. Here, SNHS biotopes (namely, geogenic reefs similar to those observed in the German Exclusive Economic Zone (EEZ) in Michaelis et al, 2019a, b) have been first observed in 2018 (OD Nature, 2018;Montereale Gavazzi et al, 2021;Montereale Gavazzi et al, 2022) and yearly followed up since.…”
Section: Northwest Study Sitementioning
confidence: 64%
See 3 more Smart Citations
“…In the current Belgian MSP (MSP; 2020-2026) it is designated as a search zone for biodiversity protection as well as a prospecting area for marine aggregate extraction. Here, SNHS biotopes (namely, geogenic reefs similar to those observed in the German Exclusive Economic Zone (EEZ) in Michaelis et al, 2019a, b) have been first observed in 2018 (OD Nature, 2018;Montereale Gavazzi et al, 2021;Montereale Gavazzi et al, 2022) and yearly followed up since.…”
Section: Northwest Study Sitementioning
confidence: 64%
“…Post-processing of underwater imagery follows the methodology described in Montereale Gavazzi et al (2021) and involves the following steps: 1) video sequencing into image stills every 10 s, 2) selection of annotatable image stills, 3) editing and enhancing imagery where needed, 4) annotation (identifying and enumerating benthic taxa), 5) georeferencing (where needed) and 6) collation of metadata. For each video transect, frames were extracted every 10 s using VLC media player (https://www.…”
Section: Post-processingmentioning
confidence: 99%
See 2 more Smart Citations
“…The acoustic signal has minimal attenuation in water, making acoustic transmission the most appropriate mechanism for transmitting information through the water column [9], [10]. Shipboard multibeam echo sounder (MBES) is rapidly becoming the most common acoustic survey tool of choice [11], [12], mainly because it allows the collection of continuous bathymetric information. High-resolution and high-precision bathymetric information is of key importance in characterizing substrate types.…”
Section: Introductionmentioning
confidence: 99%